Synthesis, characterization and photocatalytic behavior of TiO2-SiO2 mesoporous composites in hydrogen generation from water splitting - Niphadkar, P. S.; Chitale, S. K.; Sonar, S. K.; Deshpande, Suvarna S.; Joshi, P. N.; Awate, S. V. (Journal of Materials Science, 2014)
TiO2-SiO2 mesoporous composite photocatalysts with different proportions (in wt%) of TiO2 and SiO2 (TiO2-SiO2 = 20:80, 40:60, 60:40, 80:20 and 100:0) were prepared by loading TiO2 on as-synthesized Si-MCM-41 using sol-gel method. The physicochemical properties of composites were investigated by powder X-ray diffraction, N-2 adsorption-desorption measurements, transmission electron microscopy and UV-Vis diffuse reflectance spectroscopy. It is revealed that the titanium species are dispersed as TiO2 having interaction with the surface of the support. Even at high TiO2 loading, the mesostructural feature of MCM-41 was found to be intact without pore blockages. The change in morphology of TiO2 particle was observed with increase in TiO2 loading which may be due to different environment for the growth of TiO2. The photocatalytic evaluation of composites was carried out in production of hydrogen by water splitting. Among the prepared samples, mesoporous composite containing 60 % TiO2 (MTi60) has shown the best results (0.08805 mmol of H-2/h/g of TiO2) compared to other composite photocatalysts. The catalytic performance of this sample was further enhanced (similar to 8 times) after loading 1 % Pt in water splitting (0.70161 mmol of H-2/h/g of TiO2). 1 % Pt loaded on pure TiO2 (MTi100) showed hydrogen evolution of the magnitude 0.26 mmol of H-2/h/g of TiO2. TiO2-SiO2 mesoporous composite photocatalyst showed much higher activity (similar to 1.9 times) than amorphous silica-embedded titania catalyst having same composition.